Ponderings. Black notebooks - Heidegger, Martin, 1889-1976 (Studies in Continental thought., 2017)
Through these broad and sprawling notebooks, Heidegger offers fascinating opinions on Holderlin, Nietzsche, Wagner, Wittgenstein, Pascal, and many others. The importance of the Black Notebooks transcends Heidegger's relationship with National Socialism. These personal notebooks contain reflections on technology, art, Christianity, the history of philosophy, and Heidegger's attempt to move beyond that history into another beginning.